Structural and functional insights into subunit a of Saccharomyces cerevisiae V-ATPase and the Escherichia coli Alkyl Hydroperoxide Reductase complex - Phat Vinh, Dip (2014)
The new function of subunit a of the V1VO ATPase as pH sensing receptor and its regulatory binding sites, a21-17 and a2368-395 to the Sec7 domain of ARNO (ADP-ribosylation factor Nucleotide site Opener) were studied using NMR spectroscopy. The results of NMR titration experiments of mouse a21-17 and yeast a104-363 and small angle X-ray scattering (SAXS) of a104-363 suggested a new molecular mechanism between V-ATPase and ARNO in proton-pumping activity and vesicle formation. Besides pH homeostasis, regulated via V-ATPases, redox homeostasis is primary balanced via the Alkyl Hydroperoxide Reductase (AhpR). The crystal structure of both AhpR subunits, the 56 kDa subunit F (AhpF) and 21 kDa subunit C (AhpC) from Escherichia coli have been solved to 2 Å and 3.3 Å resolution. Together with AhpF SAXS analysis and cryo electron microscopy (cryoEM) studies of AhpC, the catalytic mechanism of AhpR as hydroperoxide scavenger and molecular chaperon are described in this thesis.